Multi-fractal characteristics of pore system in deep organic-rich shales of the Wufeng-Longmaxi formation in the Sichuan Basin and their geological significance - Xie, Guogen; Xie, Guoliang; Jiao, Kun (Frontiers in Earth Science, 2024)
The heterogeneity of pore system of deep shale reservoir determines the occurrence, enrichment and migration behavior of shale gas within shales. In this study, multi-fractal analysis was applied to analyze CO2 and N2 adsorption data for obtaining multi-fractal parameters including Hurst index and multi-fractal spectrum (D5--D5+) of the deep Wufeng-Longmaxi shales collected from the Sichuan Basin, China, in order to study the connectivity and heterogeneity of micropore pores and meso-macropores as well as their influencing factors. The results showed that pore system of the Wufeng-Longmaxi deep shale exhibits distinct multifractal nature. There exists significant differences in the pore volume (PV) of micropores (< 2nm), mesopore (2-50 nm), and macropore (> 50 nm) across different shale lithofacies due to their differences in TOC content and mineral composition. The heterogeneity and connectivity of micropores and meso-macropores within deep shales in the Sichuan Basin are controlled by multiple factors including shale lithofacies, burial depth, and pressure coefficients. Notably, siliceous shale (SL) and calcareous/argillaecous siliceous shale (C/ASL), known as sweet spot for current shale gas exploitation, exhibits characteristics such as relative low micropore connectivity, high micropore heterogeneity, high micropore PV and low meso-macropore connectivity. These suggest that isolated pressure-sealing compartment is easier formed within the overpressured SL and C/ASL. Thus, pressure in these shales is less likely to release during the Yanshanian-Xishanian tectonic uplift process, favoring the preservation of organic matter (OM) pores and residual interparticle pores, which is conducive to the accumulation of deep shale gas dominated by free gas.